Physical and psychological conditions in kayaking - Neldi, H.; Nasriah; Komaini, A.; Mario, D. T.; Umar, Arsil; Rasyid, W. (Journal of Human Sport & Exercise, 2023)
The effect of physical condition factors such as strength and flexibility on kayaking has been widely investigated. However, little information is found regarding psychological factors such as motivation and how they are simultaneously involved. Therefore, this research aims to analyse the elements of physical (arm muscle strength and waist flexibility) and psychological (achievement motivation) conditions on the ability to row a kayak. A total of 17 male athletes in Aceh province, Indonesia, participated in this research voluntarily. Participants were athletes registered with the Indonesian Rowing Association and had participated in championships at the provincial level (22.32 ± 1.02 years, 71.56 ± 3.64 kg, 173.09 ± 2.17 cm, and BMI 23.89 ± 2.88). Each data was collected using push and pull dynamometer tests, sit and reach tests, questionnaires, and ergometer machines. The data were then analysed using descriptive statistics, correlation, and regression analysis. The results showed that arm muscle strength, waist flexibility, and achievement motivation influenced kayak rowing ability (R = 0.933; F = 29.17; p < .05). Partially, the influence value of arm muscle strength was R = 0.727; F = 16.79; t = 4.09; p < .05, waist flexibility was R = 0.695; F = 14.04; t = 3.74; p < .05, and achievement motivation was R = 0.817; F = 30.13; t = 5.48; p < .05. Of these three elements, motivation was reported as the most dominant element, followed by arm muscle strength and waist flexibility. Finally, it is important for coaches, athletes, and practitioners to consider these elements in achieving optimal rowing ability.